Adsorbing material as well as preparation method and application thereof

By using alumina material doped with metal elements, the three-dimensional ordered macropore-mesporous structure and the doping effect of metal elements, the problem of poor adsorption effect of existing adsorption materials on halogen ions is solved, and high-efficiency and highly selective halogen ions adsorption and regeneration are achieved.

CN119588299APending Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311165158.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing adsorption materials have poor adsorption effect on halogen ions, making it difficult to effectively remove halogen ions in water bodies, resulting in deterioration of water quality and ecological damage.

Method used

Alumina material doped with metal elements has a three-dimensional ordered macroporous-mesoporous structure. Through the doping of metal elements such as lanthanum, titanium, cerium, and zirconium, the adsorption ability of the adsorbent material to halogen ions is enhanced.

Benefits of technology

It improves the adsorption capacity and ability of the adsorbent materials to halide ions, is highly selective and easy to regenerate, and is suitable for removing halide ions in wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588299A_ABST
    Figure CN119588299A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of environmental protection, and discloses an adsorption material and a preparation method and application thereof.The adsorption material contains aluminum oxide doped with metal elements, the adsorption material is of a three-dimensional ordered macroporous structure, and the metal elements are selected from one or two or more of lanthanum, titanium, cerium and zirconium. The adsorbing material disclosed by the invention has a three-dimensional ordered macroporous-mesoporous structure, so that halogen ions in a water body can flow and contact in pore channels of the adsorbing material, and the saturated adsorbing capacity of the adsorbing material can be further improved; meanwhile, according to the adsorption material, aluminum oxide is modified by adopting metal elements, so that metal cations on the surface and in pore channels of aluminum oxide are increased, and the adsorption capacity of the adsorption material on halogen ions is enhanced. Therefore, the adsorbing material provided by the invention is good in adsorbing effect on the halogen ions, high in selectivity and easy to regenerate, and has obvious competitive advantages when being used for removing the halogen ions in wastewater (such as fire-fighting wastewater and the like).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmental protection technology, and in particular to an adsorption material and a preparation method and application thereof. Background Art

[0002] Halogen elements (fluorine, chlorine, bromine, iodine) show high reactivity, strong oxidation and strong electron-withdrawing properties in molecules. They are widely used not only in cutting-edge materials and pharmaceuticals, but also in intermediate raw materials and general materials for chemical synthesis. The widespread use of halogen elements may lead to more halogen ions in industrial wastewater, which are difficult to be used by microorganisms. If high-concentration halogen-containing wastewater is directly discharged into rivers without treatment, it will destroy the natural ecological balance of the water body, deteriorate the water quality, cause serious damage to aquaculture and freshwater resources, and even pollute groundwater and drinking water sources in serious cases.

[0003] Taking fluoride ions as an example, although fluoride plays an important role in the growth of human teeth and bones, excessive intake of fluoride in the human body will seriously affect human health and quality of life, the most common being fluorosis and fluorosis; in addition, fluoride will inactivate certain enzymes in the human body, such as bone phosphorylase, glycolytic enzyme, cholinesterase, and enolase, which are important catalysts in human metabolism. In general, excessive fluoride ions are very harmful to the human body; fluoride ions in drinking water are the main source of fluoride in the human body. Therefore, my country's drinking water standards stipulate that the fluoride concentration cannot exceed 1 mg / L. Some areas can slightly lower the requirements, but the maximum cannot exceed 1.5 mg / L. Taking bromine as an example, bromide ions in waste liquid are easily oxidized to bromate ions by tap water oxidants such as chlorine. Studies have shown that adding potassium bromate to the drinking water of experimental mice will increase the chance of cancer, and will also increase non-cancerous kidney cell tumors, thyroid and peritoneal mesothelioma. Therefore, it is also necessary to control the bromide ion concentration in water bodies.

[0004] At present, the main focus is on removing fluoride ions from water bodies, and not enough attention is paid to other common halogen ions, and there are few corresponding removal technologies. Commonly used defluorination methods include precipitation, ion exchange, reverse osmosis, adsorption, etc. Among them, adsorption is the most commonly used method for removing fluoride from wastewater due to its simple process, low cost and high removal efficiency. Commonly used defluoridation agents include zeolite, activated alumina, activated carbon, bone charcoal, activated magnesium oxide, etc. However, the slow adsorption rate and low adsorption capacity of the above-mentioned defluoridation agents limit their practical applications. Therefore, the development of an adsorbent material that can efficiently adsorb halogen ions in water is of great significance for both ecological and environmental protection. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem of poor adsorption effect of adsorbent materials on halogen ions in the prior art, and to provide an adsorbent material and a preparation method and application thereof. The adsorbent material has high adsorption capacity, strong adsorption ability, high selectivity and easy regeneration for halogen ions in water.

[0006] In order to achieve the above object, the present invention provides an adsorption material on the one hand, wherein the adsorption material is aluminum oxide doped with metal elements, which has a three-dimensional ordered macroporous-mesoporous structure.

[0007] The metal element is selected from one or more of lanthanum, titanium, cerium and zirconium.

[0008] Preferably, the pore size of the macropores ranges from 50 to 400 nm, and the pore size of the mesopores ranges from 2 to 6 nm.

[0009] Preferably, the pore volume of the adsorption material is 2 to 4 mL / g.

[0010] A second aspect of the present invention provides a method for preparing an adsorbent material, the method comprising the following steps:

[0011] (1) centrifuging an emulsion containing polymethyl methacrylate microspheres, removing the supernatant, and obtaining a colloidal crystal template;

[0012] (2) mixing an aluminum source, a solvent, and a metal precursor salt to obtain a precursor solution;

[0013] (3) mixing the mesoporous template solution and the precursor solution and stirring to obtain a mixed solution;

[0014] (4) impregnating the colloidal crystal template with the mixed solution, and then drying and calcining to obtain an adsorption material having a three-dimensional ordered macroporous-mesoporous structure;

[0015] Wherein, in step (2), the metal precursor salt is selected from one or more of lanthanum salts, titanium salts, cerium salts and zirconium salts.

[0016] Preferably, the method further comprises preparing an emulsion containing polymethyl methacrylate microspheres according to the following steps:

[0017] In an argon atmosphere, deionized water is heated to 70-90° C., and then mixed with methyl methacrylate monomer to obtain a mixed solution;

[0018] The mixed solution is mixed with an initiator and reacted.

[0019] Preferably, the ratio of the amount of the methyl methacrylate monomer to the amount of deionized water is 100 g: 200-800 mL.

[0020] Preferably, the weight ratio of the methyl methacrylate monomer to the initiator is 100:0.3-2.

[0021] Preferably, the initiator is potassium persulfate.

[0022] Preferably, in step (1), the centrifugal speed is 2500-3500 rpm and the time is 3-12 hours.

[0023] Preferably, in step (2), the lanthanum salt is lanthanum nitrate and / or lanthanum chloride, preferably lanthanum nitrate.

[0024] Preferably, in step (2), the titanium salt is tetrabutyl titanate and / or titanium chloride, preferably tetrabutyl titanate.

[0025] Preferably, in step (2), the cerium salt is cerium nitrate and / or cerous chloride, preferably cerium nitrate.

[0026] Preferably, in step (2), the zirconium salt is zirconium oxychloride and / or zirconium nitrate, preferably zirconium oxychloride.

[0027] Preferably, in step (2), the molar ratio of the aluminum source, the solvent and the metal precursor is 1:2-5:0.05-1.0.

[0028] Preferably, the aluminum source is selected from one or more of aluminum isopropoxide, aluminum nitrate and aluminum chloride hexahydrate.

[0029] Preferably, the solvent is selected from one or more of ethanol, isopropanol and methanol.

[0030] Preferably, the weight ratio of the aluminum source to the mesoporous template in the mesoporous template solution is 1:0.05-0.4.

[0031] Preferably, in step (3), the mesoporous template solution contains ethanol and a mesoporous template.

[0032] Preferably, in step (3), the mesoporous template agent is selected from one or more of P123, F127 and CTAB.

[0033] Preferably, step (4) specifically comprises: using the mixed solution to impregnate the colloidal crystal template, and then drying, washing, filtering, drying and calcining.

[0034] Preferably, in step (4), the calcination process comprises: heating the dried product to 300-350°C at a rate of 0.5-3°C, maintaining the temperature for 0-4h, and then continuing to heat the product to 500-650°C, maintaining the temperature for 4-10h.

[0035] The third aspect of the present invention provides an adsorption material obtained by the method as described above.

[0036] A fourth aspect of the present invention provides a use of the adsorption material as described above in adsorbing halogen ions in water.

[0037] In the present invention, the adsorbent material has a three-dimensional ordered macroporous-mesoporous structure, which is conducive to the flow and contact of halogen ions in the water body in its pores, thereby facilitating the improvement of the saturated adsorption capacity of the adsorbent material; at the same time, the adsorbent material uses metal elements to modify aluminum oxide to increase the metal cations on the surface and in the pores of aluminum oxide, thereby enhancing the adsorption capacity of the adsorbent material for halogen ions. Therefore, the adsorbent material provided by the present invention has a good adsorption effect on halogen ions and has obvious competitive advantages when used to remove halogen ions in wastewater (such as firefighting wastewater, etc.). BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a SEM image of the adsorbent material prepared in Example 1 of the present invention;

[0039] Figure 2 is a TEM image of the adsorbent material prepared in Example 1 of the present invention;

[0040] Figure 3 is a pore size distribution diagram of the adsorbent material prepared in Example 1 of the present invention tested by mercury intrusion porosimetry;

[0041] Figure 4 The adsorption-desorption curve of the adsorbent material prepared in Example 1 of the present invention is tested by N2 adsorption-desorption;

[0042] Figure 5 This is a pore size distribution diagram of the adsorption material prepared in Example 1 of the present invention using N2 adsorption-desorption test. DETAILED DESCRIPTION

[0043] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0044] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0045] The adsorption material described in the present invention is aluminum oxide doped with metal elements, and the adsorption material has a three-dimensional ordered macroporous-mesoporous structure, wherein the metal element is selected from one or more of lanthanum, titanium, cerium and zirconium.

[0046] At present, the adsorption mechanism of common adsorbent materials (such as alumina, layered double hydrotalcite, zeolite, etc.) for removing halogen ions (such as fluorine) mainly focuses on the exchange of hydroxyl groups with pollutants, so that the adsorption performance of the adsorbent material is significantly affected by pH value and coexisting ions. In the present invention, the adsorbent material surface has abundant hydroxyl functional groups, which can play a good adsorption role on halogen ions in water, and through the doping of lanthanum, titanium, cerium, and zirconium heteroatoms, the metal defect sites in the adsorbent material are effectively increased. In addition, heteroatoms such as lanthanum have a very strong affinity with halogen ions with high electronegativity, and can improve the adsorption capacity of halogen ions through coordinated covalent bonds; at the same time, the adsorbent material with a three-dimensional ordered macroporous-mesoporous structure is conducive to the flow and contact of halogen ions in its pores, thereby improving the removal efficiency of halogen ions.

[0047] In addition, the adsorbent material of the present invention can be recycled after being regenerated with a low-concentration sodium hydroxide (sodium bicarbonate) solution. Specifically, the regeneration process of the adsorbent material is actually the reverse reaction of the adsorption of halogen ions, that is, the anion (halogen ion) compound adsorbed on the surface and inside the pores of the aluminum oxide undergoes an ion exchange reaction with the anion in the sodium bicarbonate solution, thereby restoring the active sites of the aluminum oxide and enabling recycling.

[0048] In the present invention, metal elements such as lanthanum, titanium, cerium and zirconium are selected to facilitate their doping into alumina, and these elements are variable valence metals, which are beneficial to improving the adsorption capacity of the adsorbent material for halogen ions. For example, when lanthanum metal is used for doping, the atomic radius of the lanthanum element is large and it is easy to lose electrons in the outer layer s, 5d or 4f', thereby showing a very strong affinity for halogen ions with higher electronegativity.

[0049] In the adsorption material of the present invention, the pore size of the macropores ranges from 50 to 400 nm.

[0050] In the adsorption material of the present invention, the pore size of the mesopores is 2-6 nm, and the average pore size is about 5 nm.

[0051] In the adsorption material described in the present invention, the pore volume of the adsorption material is 2-4 mL / g, preferably 3-3.5 mL / g, specifically, for example, it can be 3 mL / g, 3.1 mL / g, 3.2 mL / g, 3.3 mL / g, 3.4 mL / g or 3.5 mL / g.

[0052] The present invention also provides a method for preparing an adsorbent material. In one embodiment, the method comprises the following steps:

[0053] (1) centrifuging an emulsion containing polymethyl methacrylate microspheres, removing the supernatant, and obtaining a colloidal crystal template;

[0054] (2) mixing an aluminum source, a solvent, and a metal precursor salt to obtain a precursor solution;

[0055] (3) mixing the mesoporous template solution and the precursor solution and stirring to obtain a mixed solution;

[0056] (4) impregnating the colloidal crystal template with the mixed solution, and then drying and calcining to obtain an adsorption material having a three-dimensional ordered macroporous-mesoporous structure;

[0057] Wherein, in step (2), the metal precursor salt is selected from one or more of lanthanum salts, titanium salts, cerium salts and zirconium salts.

[0058] In the method described in the present invention, aluminum oxide is modified by using metal elements (i.e., metal precursor salts) to increase metal cations on the surface and in the pores of aluminum oxide, which can enhance the interaction between the adsorbent material and the halogen ions, thereby improving the adsorption capacity of halogen ions.

[0059] In the method described in the present invention, by preparing the adsorbent material into a three-dimensional ordered macroporous-mesoporous structure, the flow and contact of halogen ions in the water body in the pores thereof can be facilitated, thereby facilitating the improvement of the saturated adsorption capacity of the adsorbent material.

[0060] In addition, the adsorbent material prepared by the method of the present invention can be recycled after being regenerated by a low-concentration sodium hydroxide (sodium bicarbonate) solution. Specifically, the regeneration process of the adsorbent material is actually the reverse reaction of the adsorption of halogen ions, that is, the anion halogen ion (halogen ion) compound adsorbed on the surface of aluminum oxide and inside the pores undergoes an ion exchange reaction with the anion in the sodium bicarbonate solution, so that the active sites of aluminum oxide can be restored and can be recycled.

[0061] In the method of the present invention, the metal element is doped into the alumina by an in-situ synthesis method. Specifically, in the process of synthesizing alumina, the metal element is added to the reaction system, and the metal element is loaded onto the alumina powder while the alumina is formed. In the adsorption material prepared by the in-situ synthesis method, the interaction between the alumina and the active ingredient is relatively large, which is mainly because the heteroatoms occupy the lattice position in the alumina crystal, are not easy to fall off during the adsorption and catalytic process, and have little effect on the pore structure of the alumina.

[0062] The present invention does not limit the specific source of the emulsion containing polymethyl methacrylate microspheres in step (1), which can be prepared according to conventional methods in the art. In order to make the polymethyl methacrylate microspheres in the emulsion containing polymethyl methacrylate microspheres monodisperse and uniform in particle size, the present invention adopts soap-free emulsion polymerization to prepare them. In a preferred embodiment, the method further comprises preparing the emulsion containing polymethyl methacrylate microspheres according to the following steps:

[0063] Step A1, in an argon atmosphere, heating deionized water to 70-90° C., and then mixing with methyl methacrylate (MMA) monomer to obtain a mixed solution;

[0064] Step A2: mixing the mixed solution with an initiator and reacting them.

[0065] In the method of the present invention, the ratio of the amount of the methyl methacrylate monomer to the amount of deionized water is 100 g: 100-800 mL, preferably 100 g: 200-400 mL.

[0066] In the method of the present invention, the weight ratio of the methyl methacrylate monomer to the initiator is 100:0.3-2.

[0067] In a preferred embodiment, the initiator is potassium persulfate. Further preferably, the potassium of the initiator needs to be dissolved in deionized water before adding the initiator.

[0068] In a specific embodiment, step A1 includes: adding deionized water to a four-necked flask, adjusting the height of the mechanical stirring paddle, setting the stirring speed, and introducing argon; heating a constant temperature water bath to 70-90° C.; and then adding MMA monomer to obtain a mixed solution.

[0069] In a preferred embodiment, in step A2, the reaction time is 1 to 4 hours, specifically, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours or 4 hours.

[0070] In a preferred embodiment, the reaction solution obtained in step A2 is filtered using a 0.2 μm to 0.5 μm microporous filter membrane to remove the cross-linked larger polymethyl methacrylate (PMMA) microspheres, and the obtained filtrate is an emulsion containing polymethyl methacrylate (PMMA) microspheres.

[0071] In the method of the present invention, in step (1), the centrifugal speed is 2500-3500 rpm, preferably 2800-3200 rpm; the centrifugal time is 3-12 h, preferably 6-10 h.

[0072] In a preferred embodiment, the lanthanum salt is lanthanum nitrate and / or lanthanum chloride, more preferably lanthanum nitrate.

[0073] In a preferred embodiment, the titanium salt is tetrabutyl titanate and / or titanium chloride, more preferably tetrabutyl titanate.

[0074] In a preferred embodiment, the cerium salt is cerium nitrate and / or cerous chloride, more preferably cerium nitrate.

[0075] In a preferred embodiment, the zirconium salt is zirconium oxychloride and / or zirconium nitrate, more preferably zirconium oxychloride.

[0076] In a preferred embodiment, in step (2), the molar ratio of the aluminum source, the solvent and the metal precursor is 1:2-5:0.05-1.0.

[0077] In a preferred embodiment, the aluminum source is selected from one or more of aluminum isopropoxide, aluminum nitrate and aluminum chloride hexahydrate.

[0078] In a preferred embodiment, the solvent is selected from one or more of ethanol, isopropanol and methanol, more preferably ethanol.

[0079] In a preferred embodiment, the weight ratio of the aluminum source to the mesoporous template in the mesoporous template solution is 1:0.05-0.4.

[0080] In a preferred embodiment, in step (3), the mesoporous template solution contains ethanol and a mesoporous template.

[0081] In a preferred embodiment, in step (3), the mesoporous template agent is selected from one or more of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), F127 (polyethylene glycol-polypropylene glycol-polyethylene glycol) and CTAB (hexadecyltrimethylammonium bromide).

[0082] In a preferred embodiment, step (4) specifically comprises: using the mixed solution to impregnate the colloidal crystal template, and then drying, washing, filtering, drying, and calcining.

[0083] In specific implementation, step (4) includes: using the mixed solution to impregnate the colloidal crystal template, and then placing it in a constant temperature vacuum drying oven for drying. After the solvent gradually evaporates, the obtained sample is rinsed with ethanol to remove unreacted residual metal ions, and then drained with a Buchner funnel. After that, the product is placed in an oven for thorough drying, and then transferred to a tubular furnace for calcination.

[0084] In a preferred embodiment, in step (4), the calcination process comprises: heating the dried product to 300-350°C at a rate of 0.5-3°C, maintaining the temperature for 0-4h, and then continuing to heat the dried product to 500-650°C, maintaining the temperature for 4-10h.

[0085] Further preferably, in step (4), the calcination process comprises: heating the dried product to 300-350°C at a rate of 0.5-3°C, maintaining the temperature for 2-4 hours, and then continuing to heat the product to 500-650°C, maintaining the temperature for 4-8 hours.

[0086] The present invention also proposes an adsorption material obtained by the above method. The specific content of the method refers to the above embodiment. Since the adsorption material adopts all the technical solutions of all the above embodiments, it at least has all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0087] The present invention also proposes an application of the above-mentioned adsorption material in adsorbing halogen ions in water. The adsorption material has high adsorption capacity, strong adsorption ability, high selectivity, easy regeneration, and a wide pH range, and can be well applied to adsorb halogen ions in water.

[0088] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0089] Example 1

[0090] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.5 g of potassium persulfate to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0091] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0092] (3) mixing aluminum isopropoxide, ethanol and lanthanum nitrate in a molar ratio of 1:4:0.08 to obtain a precursor solution;

[0093] (4) using ethanol as a solvent, preparing a P123 solution with a mass concentration of 50 g / L, adding the P123 solution dropwise into the above-mentioned precursor solution, and slowly stirring until it is in a sol state to obtain a mixed solution, wherein the weight ratio of the amount of aluminum isopropoxide in the precursor solution to the amount of P123 in the P123 solution is 1:0.2;

[0094] (5) Immersing the colloidal crystal template in the mixed solution for 60 min, drying in a constant temperature 40° C. vacuum drying oven, taking out the sample after the solvent gradually evaporates, rinsing it with ethanol, and filtering it with a Buchner funnel to remove excess precursor solution, and then drying the product in an oven to constant weight to obtain a precursor salt complex;

[0095] (6) The composite material is mixed evenly with 20-mesh quartz sand and loaded into a quartz tube, and air is introduced. The temperature is then raised to 310°C at a rate of 2°C / min and kept constant for 3 hours. The temperature is then further raised to 650°C at a rate of 2°C / min and kept at the highest temperature for 6 hours. The temperature is then naturally lowered to obtain a three-dimensional ordered macroporous-mesoporous structure lanthanum-doped alumina material, i.e., an adsorption material.

[0096] Example 2

[0097] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 120 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 1.8 g of potassium persulfate to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0098] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0099] (3) mixing aluminum isopropoxide, ethanol and lanthanum nitrate in a molar ratio of 1:4:0.08 to obtain a precursor solution;

[0100] (4) using ethanol as a solvent, preparing a P123 solution with a mass concentration of 50 g / L, and then adding the solution dropwise to the above-mentioned precursor solution, slowly stirring until it is in a sol state, to obtain a mixed solution, wherein the weight ratio of the amount of aluminum isopropoxide in the precursor solution to the amount of P123 in the P123 solution is 1:0.4;

[0101] (5) Immersing the colloidal crystal template in the mixed solution for 50 min, drying in a constant temperature 40° C. vacuum drying oven, taking out the sample after the solvent gradually evaporates, rinsing it with ethanol, and filtering it with a Buchner funnel to remove excess precursor solution, and then placing the product in an oven to dry to constant weight to obtain a precursor salt complex;

[0102] (6) The composite material is mixed evenly with 20-mesh quartz sand and loaded into a quartz tube, and air is introduced. The temperature is then raised to 310°C at a rate of 2°C / min and kept constant for 3 hours. The temperature is then further raised to 650°C at a rate of 2°C / min and kept at the highest temperature for 6 hours. The temperature is then naturally lowered to obtain a three-dimensional ordered macroporous-mesoporous structure lanthanum-doped alumina material, i.e., an adsorption material.

[0103] Example 3

[0104] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.8 g of potassium persulfate to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0105] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0106] (3) mixing aluminum isopropoxide, ethanol and lanthanum nitrate in a molar ratio of 1:4:0.3 to obtain a precursor solution;

[0107] (4) using ethanol as a solvent, preparing a P123 solution with a mass concentration of 50 g / L, and then adding the solution dropwise to the precursor solution, slowly stirring until it is in a sol state, to obtain a mixed solution, wherein the weight ratio of the amount of aluminum isopropoxide in the precursor solution to the amount of P123 in the P123 solution is 1:0.25;

[0108] (5) Immersing the colloidal crystal template in the above mixed solution for 40 minutes, placing it in a constant temperature 40°C vacuum drying oven to dry, after the solvent gradually evaporates, taking out the sample, rinsing it with ethanol, and filtering it with a Buchner funnel to remove excess precursor solution, and then placing the product in an oven to dry to constant weight to obtain a precursor salt complex;

[0109] (6) The composite material is mixed evenly with 20-mesh quartz sand and loaded into a quartz tube, and air is introduced. The temperature is then raised to 310°C at a rate of 2°C / min and kept constant for 3 hours. The temperature is then further raised to 650°C at a rate of 2°C / min and kept at the highest temperature for 6 hours. The temperature is then naturally lowered to obtain a three-dimensional ordered macroporous-mesoporous structure lanthanum-doped alumina material, i.e., an adsorption material.

[0110] Example 4

[0111] (1) Add 400 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.5 g of potassium persulfate to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0112] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0113] (3) mixing aluminum isopropoxide, ethanol and lanthanum nitrate in a molar ratio of 1:2:0.05 to obtain a precursor solution;

[0114] (4) using ethanol as a solvent, preparing a P123 solution with a mass concentration of 50 g / L, adding the P123 solution dropwise into the above-mentioned precursor solution, and slowly stirring until it is in a sol state to obtain a mixed solution, wherein the weight ratio of the amount of aluminum isopropoxide in the precursor solution to the amount of P123 in the P123 solution is 1:0.05;

[0115] (5) Immersing the colloidal crystal template in the above mixed solution for 40 minutes, placing it in a constant temperature 40°C vacuum drying oven to dry, after the solvent gradually evaporates, taking out the sample, rinsing it with ethanol, and filtering it with a Buchner funnel to remove excess precursor solution, and then placing the product in an oven to dry to constant weight to obtain a precursor salt complex;

[0116] (6) The composite material is mixed evenly with 20-mesh quartz sand and loaded into a quartz tube, and air is introduced. The temperature is then raised to 310°C at a rate of 2°C / min and kept constant for 3 hours. The temperature is then further raised to 550°C at a rate of 2°C / min and kept at the highest temperature for 6 hours. The temperature is then naturally lowered to obtain a three-dimensional ordered macroporous-mesoporous structure lanthanum-doped alumina material, i.e., an adsorption material.

[0117] Example 5

[0118] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 90° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 1.0 g of potassium persulfate to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0119] (2) centrifuging the PMMA microsphere emulsion at 3000 rpm for 11 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0120] (3) mixing aluminum isopropoxide, ethanol and lanthanum nitrate in a molar ratio of 1:4:0.05 to obtain a precursor solution;

[0121] (4) using ethanol as a solvent, preparing a P123 solution with a mass concentration of 50 g / L, adding the P123 solution dropwise into the above-mentioned precursor solution, and slowly stirring until it is in a sol state to obtain a mixed solution, wherein the weight ratio of the amount of aluminum isopropoxide in the precursor solution to the amount of P123 in the P123 solution is 1:0.2;

[0122] (5) Immersing the colloidal crystal template in the mixed solution for 60 min, drying in a constant temperature 40° C. vacuum drying oven, taking out the sample after the solvent gradually evaporates, rinsing it with ethanol, and filtering it with a Buchner funnel to remove excess precursor solution, and then drying the product in an oven to constant weight to obtain a precursor salt complex;

[0123] (6) The composite material is mixed evenly with 20-mesh quartz sand and loaded into a quartz tube, and air is introduced. The temperature is then raised to 310°C at a rate of 2°C / min and kept constant for 3 hours. The temperature is then further raised to 650°C at a rate of 2°C / min and kept at the highest temperature for 6 hours. The temperature is then naturally lowered to obtain a three-dimensional ordered macroporous-mesoporous structure lanthanum-doped alumina material, i.e., an adsorption material.

[0124] Example 6

[0125] (1) Add 200 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.5 g of potassium persulfate to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0126] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0127] (3) mixing aluminum isopropoxide, ethanol and tetrabutyl titanate in a molar ratio of 1:5:0.2 to obtain a precursor solution;

[0128] (4) using ethanol as a solvent, preparing a P123 solution with a mass concentration of 50 g / L, adding the P123 solution dropwise into the above-mentioned precursor solution, and slowly stirring until it is in a sol state to obtain a mixed solution, wherein the weight ratio of the amount of aluminum isopropoxide in the precursor solution to the amount of P123 in the P123 solution is 1:0.15;

[0129] (5) Immersing the colloidal crystal template in the above mixed solution for 90 minutes, placing it in a constant temperature 40°C vacuum drying oven to dry, after the solvent gradually evaporates, taking out the sample, rinsing it with ethanol, and filtering it with a Buchner funnel to remove excess precursor solution, and then placing the product in an oven to dry to constant weight to obtain a precursor salt complex;

[0130] (6) The composite material is mixed evenly with 20-mesh quartz sand and loaded into a quartz tube, and air is introduced. The temperature is then raised to 310°C at a rate of 2°C / min and kept constant for 3 hours. The temperature is then further raised to 650°C at a rate of 2°C / min and kept at the highest temperature for 6 hours. The temperature is then naturally lowered to obtain a three-dimensional ordered macroporous-mesoporous structure lanthanum-doped alumina material, i.e., an adsorption material.

[0131] Example 7

[0132] The method described in Example 1 is followed, except that the lanthanum nitrate in step (3) is replaced by cerium nitrate.

[0133] Example 8

[0134] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.7 g of potassium persulfate to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0135] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0136] (3) mixing aluminum isopropoxide, ethanol and lanthanum nitrate in a molar ratio of 1:4:0.1 to obtain a precursor solution;

[0137] (4) using ethanol as a solvent, preparing a P123 solution with a mass concentration of 50 g / L, adding the P123 solution dropwise into the above-mentioned precursor solution, and slowly stirring until it is in a sol state to obtain a mixed solution, wherein the weight ratio of the amount of aluminum isopropoxide in the precursor solution to the amount of P123 in the P123 solution is 1:0.2;

[0138] (5) Immersing the colloidal crystal template in the mixed solution for 60 min, drying in a constant temperature 40° C. vacuum drying oven, taking out the sample after the solvent gradually evaporates, rinsing it with ethanol, and filtering it with a Buchner funnel to remove excess precursor solution, and then drying the product in an oven to constant weight to obtain a precursor salt complex;

[0139] (6) The composite material is mixed evenly with 20-mesh quartz sand and loaded into a quartz tube, and air is introduced. The temperature is then raised to 320°C at a rate of 2°C / min and kept constant for 3 hours. The temperature is then further raised to 640°C at a rate of 2°C / min and kept at the highest temperature for 6 hours. The temperature is then naturally lowered to obtain a three-dimensional ordered macroporous-mesoporous structure lanthanum-doped alumina material, i.e., an adsorption material.

[0140] Example 9

[0141] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.8 g of potassium persulfate to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0142] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0143] (3) mixing aluminum isopropoxide, ethanol and lanthanum nitrate in a molar ratio of 1:4:0.2 to obtain a precursor solution;

[0144] (4) using ethanol as a solvent, preparing a P123 solution with a mass concentration of 50 g / L, adding the P123 solution dropwise into the above-mentioned precursor solution, and slowly stirring until it is in a sol state to obtain a mixed solution, wherein the weight ratio of the amount of aluminum isopropoxide in the precursor solution to the amount of P123 in the P123 solution is 1:0.3;

[0145] (5) Immersing the colloidal crystal template in the mixed solution for 60 min, drying in a constant temperature 40° C. vacuum drying oven, taking out the sample after the solvent gradually evaporates, rinsing it with ethanol, and filtering it with a Buchner funnel to remove excess precursor solution, and then drying the product in an oven to constant weight to obtain a precursor salt complex;

[0146] (6) The composite material is mixed evenly with 20-mesh quartz sand and loaded into a quartz tube, and air is introduced. The temperature is then raised to 310°C at a rate of 2°C / min and kept constant for 3 hours. The temperature is then further raised to 650°C at a rate of 2°C / min and kept at the highest temperature for 6 hours. The temperature is then naturally lowered to obtain a three-dimensional ordered macroporous-mesoporous structure lanthanum-doped alumina material, i.e., an adsorption material.

[0147] Example 10

[0148] The method described in Example 1 is used for implementation, except that step (6) is as follows: the composite is mixed with 20-mesh quartz sand and evenly loaded into a quartz tube, air is introduced, and then the temperature is increased to 350°C at a rate of 3°C / min, maintained at a constant temperature for 2 hours, and then the temperature is continued to be increased to 650°C at a rate of 3°C / min, maintained at the highest temperature for 5 hours, and cooled naturally to obtain a three-dimensional ordered macroporous-mesoporous structure lanthanum-doped alumina material, i.e., an adsorption material.

[0149] Comparative Example 1

[0150] The method described in Example 1 was followed, except that the adsorption material was not in-situ modified with metal elements.

[0151] Specifically, the method for preparing the adsorption material without in-situ modification comprises the following steps:

[0152] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.5 g of potassium persulfate to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0153] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0154] (3) mixing aluminum isopropoxide and ethanol in a molar ratio of 1:4 to obtain a precursor solution;

[0155] (4) Using ethanol as solvent, prepare a P123 solution with a mass concentration of 50 g / L. Then add it dropwise into the above-mentioned precursor solution, slowly stir until it is in a sol state, and obtain a mixed solution, wherein the weight ratio of aluminum isopropoxide in the precursor solution to P123 in the P123 solution is 1:0.2;

[0156] (5) Immersing the colloidal crystal template in the mixed solution for 60 min, drying in a constant temperature 40° C. vacuum drying oven, taking out the sample after the solvent gradually evaporates, rinsing it with ethanol, and filtering it with a Buchner funnel to remove excess precursor solution, and then drying the product in an oven to constant weight to obtain a composite;

[0157] (6) The composite material is mixed evenly with 20-mesh quartz sand and loaded into a quartz tube, and air is introduced. The temperature is then raised to 310°C at a rate of 2°C / min and kept constant for 3 hours. The temperature is then further raised to 650°C at a rate of 2°C / min and kept at the highest temperature for 6 hours. The temperature is then naturally lowered to obtain an alumina material with a three-dimensional ordered macroporous-mesoporous structure, i.e., an adsorption material.

[0158] Comparative Example 2

[0159] The adsorption material is a lanthanum-doped alumina material with a three-dimensional ordered macroporous structure. The preparation method of the adsorption material comprises the following steps:

[0160] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.5 g of potassium persulfate to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0161] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 6 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0162] (3) mixing aluminum isopropoxide, ethanol and lanthanum nitrate in a molar ratio of 1:4:0.08 to obtain a precursor solution;

[0163] (4) Immersing the colloidal crystal template in the above-mentioned precursor solution for 60 minutes, placing it in a constant temperature 40°C vacuum drying oven to dry, after the solvent gradually evaporates, taking out the sample, rinsing it with ethanol, and filtering it with a Buchner funnel to remove excess precursor solution, and then placing the product in an oven to dry to constant weight to obtain a precursor salt complex;

[0164] (5) The composite material is mixed evenly with 20-mesh quartz sand and loaded into a quartz tube, air is introduced, and then the temperature is increased to 310° C. at a rate of 2° C. / min, and the temperature is kept constant for 3 h. Then, the temperature is further increased to 650° C. at a rate of 2° C. / min, and the highest temperature is maintained for 6 h. The temperature is naturally cooled to obtain a lanthanum-doped alumina material with a three-dimensional ordered macroporous structure, i.e., an adsorption material.

[0165] Comparative Example 3

[0166] The adsorption material is a lanthanum-doped alumina material with a non-three-dimensional ordered macroporous structure. Specifically, the preparation method of the adsorption material comprises the following steps:

[0167] (1) Aluminum isopropoxide, ethanol and lanthanum nitrate are mixed uniformly in a molar ratio of 1:4:0.08 to obtain a precursor solution; a small amount of the precursor solution is placed in a crucible, kept in an oven at 50°C until dry, then moved to a muffle furnace and heated to 310°C at a rate of 2°C / min, kept at the constant temperature for 3 hours, then continued to heat to 650°C at a rate of 2°C / min, maintained at the highest temperature for 6 hours, and cooled naturally to obtain a disordered lanthanum-doped alumina material, i.e., an adsorption material.

[0168] Test Example 1

[0169] The adsorbent material prepared in Example 1 was tested using a scanning electron microscope (SEM) and a transmission electron microscope (TEM). The results are as follows: Figure 1 and Figure 2 As shown by Figure 1 and Figure 2 It can be seen that the adsorbent material has a regular three-dimensional ordered macroporous structure, the pores are three-dimensionally ordered and connected, the pore size is uniform, the pore wall thickness is uniform, and a clearly visible small pore window is displayed under each macropore, with a pore size of approximately 290 to 310 nm. Figure 2 It can be clearly seen that there are a large number of ordered mesoporous structures on the walls of the macropores.

[0170] The pore size distribution of the adsorbent material was determined by mercury intrusion porosimetry. Figure 3 As shown, it is calculated that the macropore diameter of the adsorption material is distributed in the range of 70 to 380 nm, the most probable pore diameter is about 125 nm, and the pore volume is 3.1 mL / g.

[0171] The adsorption-desorption curve and mesopore size distribution of the adsorbent material were determined by nitrogen adsorption-desorption. The results are as follows: Figure 4 and Figure 5 As shown, the adsorption material exhibits an obvious hysteresis loop in the range of P / P0=0.4-0.9, the mesopore size distribution is narrow, concentrated in the range of 2-6nm, and the average pore size is about 5nm.

[0172] Test Example 2

[0173] Test of fluoride ion adsorption capacity

[0174] The adsorption capacity of the adsorbent materials prepared in Examples 1-10 and Comparative Examples 1-3 was tested, and the test method was as follows: 250 mL of an aqueous solution with a fluoride ion concentration of 20 mg / L was prepared, the pH in the system was adjusted to 7, 0.1 g of the adsorbent material was added, the mixture was stirred evenly, stirred for 2 h, the adsorbent was filtered out, and the fluoride ion concentration before and after adsorption was measured using an inductively coupled plasma spectrometer, and the fluoride ion adsorption amount was calculated according to the following formula. The results are shown in Table 1.

[0175] Adsorption amount (mg / g) = (C0-C1)V / (m×1000)mg / g;

[0176] Wherein, C0 refers to the initial concentration of fluoride ions (mg / L), C1 refers to the concentration of fluoride ions after adsorption equilibrium (mg / L); V is the volume of the fluoride-containing aqueous solution (mL); and m is the dosage of the adsorbent material (g).

[0177] Table 1

[0178] sample Fluoride ion adsorption (mg / g) Example 1 36.2 Example 2 38.9 Example 3 40.3 Example 4 33.2 Example 5 34.1 Example 6 35.3 Example 7 35.7 Example 8 34.7 Example 9 39.2 Example 10 33.8 Comparative Example 1 23.5 Comparative Example 2 18.8 Comparative Example 3 14.8

[0179] It can be seen from Table 1 that after 0.1 g of the adsorbent material prepared in the embodiment of the present invention reacted in 250 mL of a solution with a fluoride ion concentration of 20 mg / mL for 2 h, the amount of fluoride ions adsorbed was above 33 mg / g.

[0180] By comparing Example 1 with Comparative Example 1, it can be seen that if no metal element is used for modification, the adsorption amount of fluoride ions by the adsorbent material obtained is significantly reduced; by comparing Example 1 with Comparative Examples 2-3, it can be seen that if the adsorbent material is a non-three-dimensional ordered macroporous-mesoporous structure, the adsorption amount of fluoride ions is greatly reduced.

[0181] Test Example 3

[0182] Test of chloride ion adsorption capacity

[0183] The adsorption capacity of the adsorbent materials prepared in Examples 1-10 and Comparative Examples 1-3 was tested, and the test method was as follows: 250 mL of an aqueous solution with a chloride ion concentration of 60 mg / L was prepared, the pH in the system was adjusted to 7, 0.1 g of the adsorbent material was added, the mixture was stirred evenly, stirred for 2 h, the adsorbent was filtered out, and the fluoride ion concentration before and after adsorption was measured using an inductively coupled plasma spectrometer, and the fluoride ion adsorption amount was calculated according to the following formula. The results are shown in Table 2.

[0184] Adsorption amount (mg / g) = (C0-C1)V / (m×1000)mg / g;

[0185] Wherein, C0 refers to the initial concentration of fluoride ions (mg / L), C1 refers to the concentration of fluoride ions after adsorption equilibrium (mg / L); V is the volume of the fluoride-containing aqueous solution (mL); and m is the dosage of the adsorbent material (g).

[0186] Table 2

[0187]

[0188]

[0189] It can be seen from Table 2 that after 2 hours of reaction, the chloride ion adsorption amount of Examples 1-10 is above 118 mg / g, and the performance of adsorbing chloride ions is good.

[0190] Test Example 4

[0191] The adsorbent material obtained in Examples 1-10 was subjected to a regeneration effect test, and the regeneration treatment was as follows: the adsorbent was washed with deionized water and dried. The adsorbent was placed in a beaker, 30 mL of 1 mol / L NaOH was added, heated in a 25°C water bath, magnetically stirred, and the desorption time was 2 h. The adsorbent was then washed with deionized water again and dried. The adsorbent material after the regeneration treatment was tested for fluoride ion and chloride ion adsorption performance using the methods of Test Example 1 and Test 2, respectively, and the results are shown in Table 3.

[0192] Table 3

[0193] sample Fluoride ion adsorption (mg / g) Chloride ion adsorption (mg / g) Example 1 31.5 115.8 Example 2 34.2 117.6 Example 3 36.3 121.8 Example 4 28.2 105.4 Example 5 29.3 110.7 Example 6 30.3 113.2 Example 7 31.2 114.5 Example 8 29.9 112.4 Example 9 34.7 118.8 Example 10 28.7 107.9

[0194] It can be seen from Table 3 that the adsorbent materials prepared in Examples 1-10 still have a relatively high ability to treat fluoride ions and chloride ions after alkali elution, indicating that the adsorbent materials provided by the present invention can be reused and have a strong regeneration ability.

[0195] Test Example 5

[0196] The adsorption materials prepared in Example 1, Example 3 and Comparative Example 1 were subjected to a selectivity test, and the test method was as follows: an aqueous film-forming foam fire extinguishing agent (purchased from Jiangsu Jiangya Fire Technology Co., Ltd.) and water were mixed in a ratio of 6:94 to form an aqueous film-forming foam mixed solution; a certain amount of sodium fluoride was added to the aqueous film-forming foam mixed solution to obtain a mixed solution, and the concentration of fluoride ions in the mixed solution was 20 mg / L; the pH value of the system was adjusted to 7; and then 0.1 g of the adsorption material was added respectively, the mixture was stirred evenly, stirred for 2 hours, the adsorbent was filtered out, and the fluoride ion concentration before and after adsorption was measured using an inductively coupled plasma spectrometer. The results are shown in Table 4.

[0197] Table 4

[0198] sample Fluoride ion adsorption (mg / g) Example 1 33.0 Example 3 37.2 Comparative Example 1 19.2

[0199] It can be seen from Table 4 that after 2 hours of reaction, the fluoride ion adsorption capacity of the adsorbent materials prepared in Example 1 and Example 3 is 33.0 mg / g and 37.2 mg / g, while that of Comparative Example 1 is only 19.2 mg / g, which indicates that the adsorbent material provided by the present invention can efficiently remove fluoride ions from fire water and has strong anti-interference ability.

[0200] It should be noted that the preparation principles of Example 2 and Examples 4-10 are similar to those of Examples 1 and 3, and therefore, their anti-interference capabilities are much higher than that of Comparative Example 1, and their anti-interference capabilities are strong.

[0201] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An adsorption material, characterized in that: The adsorption material is aluminum oxide doped with metal elements, which has a three-dimensional ordered macroporous-mesoporous structure. The metal element is selected from one or more of lanthanum, titanium, cerium and zirconium.

2. The adsorption material according to claim 1, characterized in that The pore size of macropores ranges from 50 to 400 nm, and the pore size of mesopores ranges from 2 to 6 nm.

3. The adsorption material according to claim 1, characterized in that The pore volume of the adsorption material is 2-4 mL / g.

4. A method for preparing an adsorbent material, characterized in that: The method comprises the following steps: (1) centrifuging an emulsion containing polymethyl methacrylate microspheres, removing the supernatant, and obtaining a colloidal crystal template; (2) mixing an aluminum source, a solvent, and a metal precursor salt to obtain a precursor solution; (3) mixing the mesoporous template solution and the precursor solution and stirring to obtain a mixed solution; (4) impregnating the colloidal crystal template with the mixed solution, and then drying and calcining to obtain an adsorption material having a three-dimensional ordered macroporous-mesoporous structure; Wherein, in step (2), the metal precursor salt is selected from one or more of lanthanum salts, titanium salts, cerium salts and zirconium salts.

5. The method according to claim 4, characterized in that The method further comprises preparing an emulsion containing polymethyl methacrylate microspheres according to the following steps: In an argon atmosphere, deionized water is heated to 70-90° C., and then mixed with methyl methacrylate monomer to obtain a mixed solution; The mixed solution is mixed with an initiator and reacted.

6. The method according to claim 5, characterized in that The ratio of the amount of methyl methacrylate monomer to deionized water is 100g:200-800mL; Preferably, the weight ratio of the methyl methacrylate monomer to the initiator is 100:0.3-2; Preferably, the initiator is potassium persulfate.

7. The method according to any one of claims 4 to 6, characterized in that: In step (1), the centrifugal speed is 2500-3500 rpm and the time is 3-12 hours.

8. The method according to any one of claims 4 to 6, characterized in that: In step (2), the lanthanum salt is lanthanum nitrate and / or lanthanum chloride, preferably lanthanum nitrate; Preferably, in step (2), the titanium salt is tetrabutyl titanate and / or titanium chloride, preferably tetrabutyl titanate; Preferably, in step (2), the cerium salt is cerium nitrate and / or cerous chloride, preferably cerium nitrate; Preferably, in step (2), the zirconium salt is zirconium oxychloride and / or zirconium nitrate, preferably zirconium oxychloride.

9. The method according to claim 4, characterized in that In step (2), the molar ratio of the aluminum source, the solvent and the metal precursor is 1:2-5:0.05-1.0; Preferably, the aluminum source is selected from one or more of aluminum isopropoxide, aluminum nitrate and aluminum chloride hexahydrate; Preferably, the solvent is selected from one or more of ethanol, isopropanol and methanol.

10. The method according to claim 4, characterized in that The weight ratio of the aluminum source to the mesoporous template in the mesoporous template solution is 1:0.05-0.4; Preferably, in step (3), the mesoporous template solution contains ethanol and a mesoporous template; Preferably, in step (3), the mesoporous template agent is selected from one or more of P123, F127 and CTAB.

11. The method according to claim 4, characterized in that Step (4) specifically includes: using the mixed solution to impregnate the colloidal crystal template, and then drying, washing, filtering, drying and calcining.

12. The method according to claim 4 or 11, characterized in that: In step (4), the calcination process includes: heating the dried product to 300-350°C at a rate of 0.5-3°C, maintaining the temperature for 0-4h, and then continuing to heat the product to 500-650°C, maintaining the temperature for 4-10h.

13. An adsorbent material obtained by the method according to any one of claims 4 to 12.

14. Use of the adsorption material according to any one of claims 1 to 3 and 13 for adsorbing halogen ions in water.

Citation Information

Patent Citations

  • Method for removing fluorine ion from water by using oxide of lanthanum-carried aluminum oxide

    CN101234792A

  • Method for preparing three-dimensional ordered macroporous aluminum oxide by two templates

    CN103864124A

  • Lanthanum-loaded activated aluminium oxide defluorinating adsorbent and preparation method thereof

    CN104923150A

  • Three-dimensional ordered macroporous-mesoporous oxide material and preparation method thereof

    CN106587077A

  • High capacity adsorbent for fluoride ion and oxyanions of phosphorous and arsenic and method for making the same

    CN106999909A